Circovírus suíno tipo 2 e Parvovírus suíno: estudo do envolvimento em alterações reprodutivas em marrãs e porcas de primeiro a terceiro parto - Alessandra Silva Dias (2010)
The involvement of porcine circovirus type 2 (PCV2) and porcine parvovirus (PPV) in reproductive failures in three swine herds (G1, G2 and G3) was studied by the association of natural infection of gilts and sows and your offspring by these viruses. Sera of 143 sows before breeding and after farrowing and of two to five newborn pre-suckle piglets of these sows were submitted to antibodies detection against PCV2 and PPV. Sows sera were submitted to viral detection against PCV2. Tissues sample of mummified fetuses and stillborn piglets from followed sows were investigated to presence of PCV2 DNA. Stomach content from stillborn piglets was tested for the presence of antibodies against PPV. There was no association between viremia to PCV2 and reproductive failures in sows, as well as between PPV antibodies increase and reproductive failures. However, there was association between occurrence of fetal abnormalities related to PCV2 and PPV and the presence of reproductive failures, as well as between the co-participation of both viruses and the presence of reproductive failures. There was transplacental infection by PCV2 and PPV in sows with high antibodies titers, generating viable and seropositive piglets, regardless of vaccination against both agents.